The Development of Sand Cement Brick Incorporating of Ceramic Tiles Waste - Johar, Muhammad Afnan Hariz; Jamaluddin, Norwati (Recent Trends in Civil Engineering and Built Environment, 2024)
Brick is a form of masonry material used to construct walls, walkways, and other structures. Sand cement brick is porous, low mechanical strength, ductile and has poor crack resistance and to utilize the use of ceramic tiles waste in the development of sand cement brick. In this study, ceramic tiles waste is used as partial replacement of sand in the production of sand cement brick. The objective to be achieved for this study is to determine the suitable percentage of replacement and properties of sand cement bricks containing ceramic tiles waste as the partial replacement for fine aggregate. To process the CTW into smaller size, hammer and LA Abrasion machine was used. The mix consist of 40% and 50% ceramic tiles waste is partially replace sand to produce samples of 36 bricks with ratio of 1:3. Furthermore, the tests carried out on the sand cement brick samples are density tests, water absorption tests and compression strength tests. In conclusion, the optimum percentage replacement of Ceramic Tiles Waste with sand are 40%. As the higher percentage replacement, the higher compressive strength and water absorption